Civilian Control of The Military in The Post-New Order Indonesia - Muhammad Fahri Riza (International Journal on Social Science, Economics and Art, 2020)
This study aims to determine how the control exercised over the military post of the new order. This study also uses descriptive method, using the historical approach will be discussed how the civilian control of the military post of the new order by using some theories, such as civil, military, civil-military relations and military orientation. Civilian control carried out against the military can be seen from the new paradigm shift military that contains redefenisi, repositioning and restructuring, then control over the military through its policies and relations civilian agencies and the military that took place during the reform such as the legislature, bureaucracy and political parties. The military paradigm shift leads to the enforcement of civil supremacy that change systematically and gradually, where the military is no longer involved in practical politics of national, work assignment abolish the military in civilian institutions and returned to the barracks as part of military professionalism. In addition, the civil administration after the new order also perform consistency for the establishment of civilian supremacy, in which the government minimize the role of the military in national politics as the policy of the Act No. 34 of 2004 which eliminates the military's involvement in the legislative body. Civilian control of the military is done after the new order does two control is to control the subjective control and control of the control objective.